Legal Protection for MSMEs in the Digital Ecosystem: A Review of E-Commerce Platforms - La Ode Mbunai (Transpublika Publisher, 2025)
Digital transformation has opened up significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand market access through e-commerce platforms. However, behind these opportunities lie complex legal challenges, such as contractual disparities, monopolistic practices, and misuse of personal data. This study aims to examine the forms of legal protection for MSMEs in the digital ecosystem, with a focus on their interactions with large digital platforms. The methods used are normative and conceptual legal analysis, with an examination of regulations such as Law No. 5 of 1999, the Information and Transactions Law (ITE Law), the Consumer Protection Law, the Personal Data Protection Law (PDP Law), and Ministry of Trade Regulation No. 31 of 2023. The results of the study indicate that although regulations are in place, their implementation has not been optimal in ensuring fairness and sustainability for SMEs. Therefore, the establishment of progressive regulations and a Digital Oversight Task Force is necessary to integrate cross-agency oversight, strengthen law enforcement, and create an inclusive and fair digital ecosystem for SMEs.